Pengaruh Konten Marketing Tiktok Grab Indonesia terhadap Customer Engagement Mahasiswa Universitas Sumatera Utara - M Simanjuntak, Frans Rochendy; Safirah, Andriani; Rahma, Ummaina; Wafi NST, Wildan (PT. Alahyan Publisher Sukabumi, 2024)
This study aims to analyze the influence of TikTok Grab Indonesia content marketing elements on customer engagement in students of the University of North Sumatra. The study used a quantitative approach with a sample of 100 respondents selected through purposive sampling techniques. The results showed that message interactivity had the most significant influence on customer engagement (P-value 0.002), followed by the posting time frame (P-value 0.044). In contrast, the topic's attractiveness did not show significant influence (P-value 0.681), while the post format was close to significant (P-value 0.079), which required further analysis. In addition, this research highlights the importance of message interactivity and content upload timing in increasing customer engagement. A marketing strategy through TikTok that emphasizes these elements can help Grab strengthen relationships with customers, especially young people. This study also recommends expanding the sample coverage in future studies to obtain more representative results.